Alkenylbenzoquinones and other compounds from the fruit of Maesa lanceolata exhibited potent cytotoxic, antibacterial, and antiradical scavenging activities§. Issue 17 (1st September 2022) - Seumo, Amanda Seumo; Nanfack, Arno Rusel D.; Ndontsa, Blanche Laure; Bitchagno, Gabin Thierry M.; Mbouangouere, Roukayatou; Lenta, Bruno N.; Sewald, Norbert; Tane, Pierre; Tene, Mathieu; Ngouela, Silvère Augustin
Abstract: A phytochemical study of the methanol extract of the fruit of Maesa lanceolata resulted in the isolation of a new alkenylbenzoquinone (1 ), alongside the known compounds ( Z )-2, 5-dihydroxy-6-methyl-3-(pentadec-10'-enyl)-1, 4-benzoquinone (2 ), 2, 5-dihydroxy-6-methyl-3-(nonadec-14'-enyl)-1, 4-benzoquinone (3 ), 2, 5-dihydroxy-6-methyl-3-(tridecyl)-1, 4-benzoquinone (4 ), (2 S, 3 S, 4 R, 2' R, 9E)-[2'-hydroxytetraeicosanoyl]-2-aminooctadec-9-ene-1, 3, 4-triol (5 ), monopalmitin (glyceryl palmitate) (6 ), lupeol (7 ), and 3- O -( β -D-glucopyranoside)- β -sitosterol (8 ). The structures of the compounds were established by the means of spectroscopic (1 D- and 2 D-NMR) and spectrometric techniques (MS). The isolated compounds were assessed for their antibacterial, cytotoxic, and antiradical activities. Compound 2 showed moderate activity against Staphylococcus warneri (DSMZ 20036), while the other compounds were inactive. The two quinones 1 and 2 were significantly cytotoxic, with IC50 values of 0.005  µ M and 12.5  µ M respectively, and were weakly active towards DPPH radical (IC50 >250  µ g/mL). Graphical Abstract: UF0001